2008
DOI: 10.1002/jmv.21245
|View full text |Cite
|
Sign up to set email alerts
|

Reliable detection and quantitation of viral nucleic acids in oral fluid: Liquid phase‐based sample collection in conjunction with automated and standardized molecular assays

Abstract: Oral fluid has been used widely as sample matrix for the detection and quantitation of viral nucleic acids. However, in the vast majority of previous studies, various methods for collection of oral fluid and molecular assays lacking automation and standardization were used. In this study, a new standardized liquid phase-based saliva collection system was employed followed by a fully automated viral nucleic acid extraction and real-time PCR using commercially available in vitro diagnostics (IVD)/Conformité Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…This collection system has been recently tested using routine laboratory methods. It has demonstrated reliable and reproducible results for measurement of calcium, magnesium ( 19 ), salivary alpha-amylase (SAA), UA ( 2 ), IgA, cortisol, drug and medication monitoring ( 33 ) and quantification of viral RNA ( 7 ). However, some analytes may suffer interference due to low pH and additives present in the extraction solution ( 2 , 33 ).…”
Section: Saliva Collection Methods and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…This collection system has been recently tested using routine laboratory methods. It has demonstrated reliable and reproducible results for measurement of calcium, magnesium ( 19 ), salivary alpha-amylase (SAA), UA ( 2 ), IgA, cortisol, drug and medication monitoring ( 33 ) and quantification of viral RNA ( 7 ). However, some analytes may suffer interference due to low pH and additives present in the extraction solution ( 2 , 33 ).…”
Section: Saliva Collection Methods and Storagementioning
confidence: 99%
“…Salivary DNA is being routinely used in many clinical laboratories for assessing the genetic susceptibility to various diseases (Table 1). Saliva based tests have been successfully used in human immunodeficiency virus (HIV) infection diagnosis ( 4 ), monitoring renal disease ( 5 ), prevention of cardiometabolic risk ( 6 ), detection and quantification of viral nucleic acids ( 7 ), forensic medicine investigations ( 8 ), dental studies ( 9 , 10 ) and drug abuse monitoring ( 8 ). There are also some studies proposing the use of saliva in monitoring physically active individuals, incremental effort test ( 2 , 11 , 12 ) and psychological stress ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have indicated the possible utility of saliva in monitoring of uric acid for cardiometabolic risk [7], drugs such as theophylline and steroids, quantitation of viral nucleic acids in herpes simplex virus DNA, varicella zoster virus DNA, and hepatitis C virus RNA [8], identification of biomarkers (IL-1β, -6, -8, TNF-α, lysozyme, MMP-8, TIMP-1) and total protein concentration in systemic diseases [9], inter alia . The non-invasiveness, ease and low-cost in collection have made saliva an attractive sample.…”
Section: Introductionmentioning
confidence: 99%
“…When cutaneous signs and symptoms are lacking, the diagnosis can only be made using serological or molecular genetic methods. In some cases the antigen could be detected by a swab of the oral mucosa and subsequent polymerase chain reaction [25]. Experience shows that affected patients consult ENT specialists and neurologists due to the pain and the cranial nerve lesions [26].…”
Section: Clinical Findingsmentioning
confidence: 99%